Disseminated Mycobacterium avium Infection Presenting with Bladder Lesions in a Patient with Interferon-γ-neutralizing Autoantibodies - Miyashita, Koichi (Intern Med, 2018)
A 63-year-old woman presented with a fever, eruption, and sterile pyuria. A cystoscopic examination revealed submucosal nodular lesions in the trigone of the bladder, and a biopsy specimen showed epithelioid cell granulomas in the lamina propria of the bladder. Mycobacterium avium grew in the urine culture. Other organ involvement, such as the lungs, spleen, bones, muscles, and pelvic lymph nodes, was observed on radiological examinations, and M. avium was isolated from some organ lesions. Interferon-γ-neutralizing autoantibodies were detected in the patient’s serum. Therefore, the patient was diagnosed with disseminated M. avium infection, which was resolved with antimycobacterial treatment.